Contemporary Spanish cinema - Jordan, Barry, 1950-; Morgan-Tamosunas, Rikki; Manchester University Press (Manchester, UK : Manchester University Press, 2019)
'Contemporary focus, right up to date with material from 1980s and 90s. Wide-ranging analyses of major directors, themes, genres and issues, including historical film, genre cinema, women in film and autonomies' --Back cover.
Preface -- Introduction -- 1. Reconstucting the past: Historical cinema in post-Pranco Spain -- 2. Cultural re-inscription: Popular genre film in post-Franco Spain -- 3. Gender and sexuality in post-Franco cinema -- 4. Recuperating nationalist identities: Film in the autonomous regions -- Conclusion -- Index.
Made available via: manchesterhive.
Includes index.
In English.
Description based on print record
JSTOR
Keywords: Motion pictures -- Spain; Cinéma -- Espagne; Film, TV and radio; Film theory and criticism; PERFORMING ARTS / Film / History & Criticism; Cine español; Motion pictures; Spain; Films; Motion pictures -- Spain -- History; The Arts -- Performing arts -- Film & cinema -- Film history, theory & criticism; PERFORMING ARTS / Film / History & Criticism; Electronic books; History